An illustrated guide to the lady beetles (Coleoptera: Coccinellidae) of the Indian Subcontinent. Part II. Tribe Chilocorini - Poorani, J. (Zootaxa, 2023)
An illustrated guide to the lady beetles of the tribe Chilocorini (Coleoptera: Coccinellidae: Coccinellinae) of the Indian region is presented. Brief diagnostic accounts of six genera and 31 species are given with supporting illustrations of the diagnostic characters, including genitalia, wherever possible. Details of distribution, host insects / plant associations, and seasonal occurrences are provided for the first time based on extensive collections, label data and published literature. Chilocorus keralensis sp. n. is described from the Western Ghats, South India. Brumoides lineatus sensu Kapur 1967, recorded from the Andaman Islands, is found to be distinct from B. lineatus Weise 1885, and described and illustrated as B. andamanensis sp. n. Phaenochilus indicus Miyatake, 1970 and P. flaviceps Miyatake, 1970 are transferred to Chilocorus Leach (comb. n.) following the latest phylogenetic generic classification of Chilocorini. Three species, Chilocorus albomarginalis (Li & Wang), Chilocorus nigricaeruleus Li & Wang and Chilocorus yunlongensis Cao & Xiao, all originally described from China, are added to the Indian fauna of Chilocorini based on material examined from the north-eastern Indian states of Assam, Meghalaya, and Manipur, respectively. For nine species, illustrations of the life stages are included to facilitate their field identification. A key to the genera and an updated and revised checklist of the Chilocorini of the Indian subcontinent are also provided.